Families' importance in nursing care-families' opinions: a cross-sectional survey study in the homecare setting - Josien M. Woldring; Wolter Paans; Reinold Gans; Laura Dorland; Marie Louise Luttik (BMC, 2024)
Abstract Background Informal care is an essential part of support provided in the homecare setting. To ensure effective healthcare provision, good communication and collaboration between informal and formal care providers are crucial. To achieve this aim, it is necessary to have a clear understanding of the perspectives of all stakeholders. In the scientific literature, limited knowledge is available regarding family members' opinions about their involvement in care. To date, no instruments have been developed that accurately measure these opinions. This study aims to elucidate the opinions of family members about their involvement in nursing care. Methods A cross-sectional survey approach was employed. The methodological steps in this study were (1) convert the Families' Importance in Nursing Care-Nurses' Attitudes (FINC-NA) from a nurses' perspective to a family perspective and thus develop the Families' Importance in Nursing Care-Families' Opinions (FINC-FO) and (2) measure families' opinions regarding their involvement in home nursing care. The questionnaire was sent to 3,800 patients with activated patient portals, which accounts for about 17% of the total patient base. Responses were received from 1,339 family members, a response rate of 35%. Results The developed FINC-FO questionnaire showed homogeneity and internal consistency. The results of the questionnaire indicate that family members consider it important to be involved in care and that they wish to be acknowledged as participants in discussions about care (planning) but are less inclined to actively participate in the provision of care by nurses. Family members expressed less explicit opinions about their own support needs. Factors such as level of education, type of partnership, and amount of care provided are seemingly associated with these opinions. Conclusions Family members in the homecare setting wish to be involved in discussions about care (planning). The transition in care from primarily formal to more informal care necessitates an awareness and clear definition-on part of both healthcare professionals and families-of their respective roles in the provision of care. Communication about wishes, expectations, and the need for support in care is essential to ensure quality of care and that the family can sustain caregiving.